Estudio de las lesiones de la selección masculina absoluta española de fútbol (2008-2015) / Study of Spanish Soccer Absolute Male Selection. pp. 667-682 - Celada, O. L.; García-Cota, J.; Herrero-González, H.; Martínez-Rodríguez, R.; Galán-del-Rio, F.; Rodríguez-Iñigo, E.; Fernández-Jaén, T. F.; Fortoul-García, M. P.; Guillen-García, P.; Lopez-Alcorocho, J. M. (Revista Internacional de Medicina y Sciencias de la Actividad y del deporte, 2021)
Lesional Incidence (LI) is known as the lesion number per 1,000 exposure hours. The aim was to determine the LI and the possible factors that could have any influence in the lesions of the Spanish male absolute selection soccer players from 2008 to 2015. During this period 85 players were convened. Exposure time was 10,450 hours of which, 8,800 hours corresponding to training sessions and 1,650 hours to competition. LI was 7.46 lesions per 1,000 exposure hours of which, 76.9% corresponded to competition matches and the remaining to training sessions. Muscle impairment was the most frequent injury (52.4%). Injury severity was significantly related to player position on the field and with lesion mechanism. In conclusion, Spanish male absolute soccer selection showed a LI in the average of the remaining top-level soccer teams in the world.